Thermodynamic Damping in Porous Materials with Spherical Cavities - Sofia D. Panteliou; Andrew D. Dimarogonas (Shock and Vibration)
When a material is subjected to an alternating stress field, there are temperature fluctuations throughout its volume due to the thermoelastic effect. The resulting irreversible heat conduction leads to entropy production that in turn is the cause of thermoelastic damping. An analytical investigation of the entropy produced during a vibration cycle due to the reciprocity of temperature rise and strain yielded the change of the material damping factor as a function of the porosity of the material. A homogeneous, isotropic, elastic bar of cylindrical shape is considered with uniformly distributed spherical cavities under alternating uniform axial stress. The analytical calculation of the dynamic characteristics of the porous structure yielded the damping factor of the bar and the material damping factor. Exsperimental results on porous metals are in good correlation with an analysis.